2022
DOI: 10.1038/s41467-022-33892-8
|View full text |Cite
|
Sign up to set email alerts
|

Designing fuel cell catalyst support for superior catalytic activity and low mass-transport resistance

Abstract: The development of low-Platinum content polymer electrolyte fuel cells (PEFCs) has been hindered by inexplicable reduction of oxygen reduction reaction (ORR) activity and unexpected O2 mass transport resistance when catalysts have been interfaced with ionomer in a cathode catalyst layer. In this study, we introduce a bottom-up designed spherical carbon support with intrinsic Nitrogen-doping that permits uniform dispersion of Pt catalyst, which reproducibly exhibits high ORR mass activity of 638 ± 68 mA mgPt−1 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
48
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 79 publications
(48 citation statements)
references
References 49 publications
0
48
0
Order By: Relevance
“…Moreover, the values corresponding to Films N200–N600 indicated that the oxygen concentration decreased and the nitrogen concentration increased with increasing NH 3 treatment temperature. These findings suggest that the NH 3 treatment replaced the O functional groups with N functional groups. …”
Section: Resultsmentioning
confidence: 95%
See 2 more Smart Citations
“…Moreover, the values corresponding to Films N200–N600 indicated that the oxygen concentration decreased and the nitrogen concentration increased with increasing NH 3 treatment temperature. These findings suggest that the NH 3 treatment replaced the O functional groups with N functional groups. …”
Section: Resultsmentioning
confidence: 95%
“…The effects of the carbon–ionomer interactions on the catalyst layer are discussed henceforth. The rigid ionomer bonding on the N-modified carbon supports presumably suppresses the ionomer poisoning of Pt catalysts in the catalyst layer, resulting in improved PEFC performance upon the use of the N-modified carbon supports in the cathode catalyst layers. Furthermore, N-modified carbon supports can reduce the amount of “nonadsorbed ionomers” in catalyst inks, which adversely affects the dispersion stability, viscosity-related properties, and the quality of the catalyst layer, emphasizing their potential role in ensuring productivity and durability of PEFCs.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…49,50 Moreover, the ultralow Pt loading (0.034 mg Pt cm À2 ) MEA with Ndoped carbon support developed by Islam et al even demonstrated less than half of pressure-independent oxygen transport resistance than the high Pt loading (0.063 mg Pt cm À2 ) MEA without that. 51…”
mentioning
confidence: 99%
“…14 More importantly, Pt-based nanoparticles (NPs) are prone to migrate and agglomerate during long-term operation, which further leads to a decrease in catalytic activity and durability. [15][16][17] To address the above-mentioned barriers, the utilization of Pt atoms can be improved by regulating the size, morphology and interaction with the support of Pt NPs, thereby improving its electrocatalytic activity and antipoisoning ability.…”
Section: Introductionmentioning
confidence: 99%